2005
DOI: 10.1080/10236660500345885
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Retardation/Relaxation Processes in Bisphenol A Polycarbonate: Thermostimulated Creep and Dynamic Mechanical Analysis Combined Investigations

Abstract: Thermostimulated creep (TSCr) and dynamic mechanical analysis (DMA) have been used to analyze the complex secondary retardation=relaxation mode of bisphenol A polycarbonate (PC). TSCr and DMA studies have been combined to extend the frequency range using the very low equivalent frequency of TSCr measurement (%10 À3 Hz). The dielectric spectra revealed a bimodal b retardation=relaxation mode with two overlapped components b 2 and b 1 . A thermal sampling (TS) protocol has been applied to TSCr measurements to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…There are works in the literature suggesting to fit the experimental data for the β relaxation processes in polyesters with more than a single HN function; Soccio et al [58], for instance, who investigated the local and segmental relaxation dynamics of poly(butylene 2,5-furanoate) (PBF), reported that local dynamics are associated with a broad relaxation that can be described by two processes, respectively related to the more mobile (glycolic) subunit and to the stiffer (acidic) moiety. This approach has been used to describe the relaxation phenomena in other polyesters in comparison with PET [59,60], as well as in different polymers such as bisphenol A polycarbonate [61]. Considering that the main difference between 2,5-PEF and 2,4-PEF was detected by Bourdet et al [31] on the local β relaxations, and that the samples in this study have a repeating unit with dipoles associated either to the furan ring (acidic moiety, expected to be less mobile) or to the glycolic subunit (expected to be more mobile) [58], all the DRS analyses were performed by fitting the experimental data with three HN functions (α, β2 and β1) plus a contribution accounting for conductivity, as illustrated in Fig.…”
Section: Molecular Mobility Evaluated By Drsmentioning
confidence: 99%
“…There are works in the literature suggesting to fit the experimental data for the β relaxation processes in polyesters with more than a single HN function; Soccio et al [58], for instance, who investigated the local and segmental relaxation dynamics of poly(butylene 2,5-furanoate) (PBF), reported that local dynamics are associated with a broad relaxation that can be described by two processes, respectively related to the more mobile (glycolic) subunit and to the stiffer (acidic) moiety. This approach has been used to describe the relaxation phenomena in other polyesters in comparison with PET [59,60], as well as in different polymers such as bisphenol A polycarbonate [61]. Considering that the main difference between 2,5-PEF and 2,4-PEF was detected by Bourdet et al [31] on the local β relaxations, and that the samples in this study have a repeating unit with dipoles associated either to the furan ring (acidic moiety, expected to be less mobile) or to the glycolic subunit (expected to be more mobile) [58], all the DRS analyses were performed by fitting the experimental data with three HN functions (α, β2 and β1) plus a contribution accounting for conductivity, as illustrated in Fig.…”
Section: Molecular Mobility Evaluated By Drsmentioning
confidence: 99%